Characterization of old paper samples exhibiting foxing - Relvas, C. (2015)
Three paper samples made of rag fibres, rag and bleached softwood fibres, and mechanical pulp, presenting foxing stains, were studied by non-destructive techniques. Fibre disruption was observed on fox spots on one of the samples, while accumulation of calcite particles occurred on another sample. The third sample presented no morphological alteration of the surface on the foxing stains. The two wood pulp papers contained kaolinite as filler and muscovite was also detected, probably due to contamination of kaolinite. Calcium sulphate is also present in one of these samples. Calcite was detected in the rag paper. Either resinaceous or proteinaceous materials were used as sizing agents. EDXRF analysis showed no differences, within the standard deviation, for the iron and copper contents in the foxed and unfoxed areas. ATR-FT-IR has shown to be an adequate technique to detect biotic attack on the stains. Five bacterial strains were isolated either from the foxed and unfoxed areas and one fungal strain belonging to the Penicillium genera was isolated from the foxed areas.